Comparative proteomics of HepG2 cells reveals NGLY1 as an important regulator of ferroptosis resistance and iron uptake - Stuart Emmerson; Haruhiko Fujihira; Takehiro Suzuki; Naoshi Dohmae; Peter Greimel; Yoshio Hirabayashi; Tadashi Suzuki (PLoS ONE, 2025)
NGLY1 deficiency is a rare genetic disorder caused by mutations in the NGLY1 gene. This disorder presents a wide range of clinical symptoms, and its severity varies among affected individuals. Previous studies have focused on understanding the influence of NGLY1 on energy metabolism, revealing dysregulation in lipid metabolism following NGLY1 deletion. In this study, we investigated the consequences of the loss of NGLY1 on ferroptosis and iron homeostasis using human hepatocellular carcinoma cells, HepG2. Comparative proteomics analysis revealed significant alterations in protein quantities in NGLY1 -deficient HepG2 cells, indicating that these cells are under “pro-ferroptotic” stress state. Moreover, dysregulated iron uptake and increased reactive oxygen species production were observed in the absence of NGLY1, indicating a novel perspective on the consequences of the loss of NGLY1 . These findings provide important insights into the molecular pathways affected by NGLY1 deletion and may contribute to the development of potential therapeutic strategies for individuals with NGLY1 deficiency.